TRANSFORMASI TATA KELOLA KEUANGAN DAN IMPLEMENTASI PENDIDIKAN AKUNTANSI SYARIAH PADA EKOSISTEM PONDOK PESANTREN ATTAQWA BEKASI - Dawud Arif Khan (DEVELOPMENT: Journal of Community Engagement, 2023)
This research report presents a comprehensive analysis regarding the urgency and implementation of financial governance transformation at Pondok Pesantren Attaqwa, Bekasi, in response to national regulatory dynamics and modernity demands. This study is motivated by the enactment of Law Number 18 of 2019 concerning Pesantren and the effectiveness of the Interpretation of Financial Accounting Standards (ISAK) 35 on January 1, 2020, which changed the financial reporting landscape of religious-based non-profit entities in Indonesia. Using the Asset-Based Community Development (ABCD) methodology, this program aims not only to standardize financial reports but also to build the economic independence of the pesantren through internal asset optimization. Field findings indicate that despite technical literacy challenges and paternalistic cultural resistance, Pesantren Attaqwa possesses strong social capital and economic assets—including the rapidly developing Pesantren-Owned Business Entity (BUMP)—to transition from trust-based accounting towards system-based accountability. This report recommends an accounting pedagogy approach based on fiqh analogy to bridge the understanding gap among asatidz, as well as the institutionalization of foundation internal regulations to ensure sustainable, transparent, and accountable governance.